Diagnosis of patients with heart failure with preserved ejection fraction in primary care: cohort study. (21st September 2021) - Forsyth, Faye; Brimicombe, James; Cheriyan, Joseph; Edwards, Duncan; Hobbs, F.D. Richard; Jalaludeen, Navazh; Mant, Jonathan; Pilling, Mark; Schiff, Rebekah; Taylor, Clare J.; Zaman, M. Justin; Deaton, Christi; et al.
Abstract: Aims: Heart failure with preserved ejection fraction (HFpEF) accounts for half of all heart failure (HF), but low awareness and diagnostic challenges hinder identification in primary care. Our aims were to evaluate the recruitment and diagnostic strategy in the Optimise HFpEF cohort and compare with recent recommendations for diagnosing HFpEF. Methods and results: Patients were recruited from 30 primary care practices in two regions in England using an electronic screening algorithm and two secondary care sites. Baseline assessment collected clinical and patient‐reported data and diagnosis by history, assessment, and trans‐thoracic echocardiogram (TTE). A retrospective evaluation compared study diagnosis with H2 FPEF score and HFA‐PEFF diagnostic algorithm. A total of 152 patients (86% primary care, mean age 78.5, 40% female) were enrolled; 93 (61%) had HFpEF confirmed. Most participants had clinical features of HFpEF, but those with confirmed HFpEF were more likely female, obese, functionally impaired, and symptomatic. Some echocardiographic findings were diagnostic for HFpEF, but no difference in natriuretic peptide levels were observed. The H2 FPEF and HFA‐PEFF scores were not significantly different by group, although confirmed HFpEF cases were more likely to have scores indicating high probability of HFpEF. Conclusions: Patients with HFpEF in primary care are difficult to identify, and greater awareness of the condition, with clear diagnostic pathways and specialist support, are needed. Use of diagnostic algorithms and scores can provide systematic approaches to diagnosis but may be challenging to apply in older multi‐morbid patients. Where diagnostic uncertainty remains, pragmatic decisions are needed regarding the value of additional testing versus management of presumptive HFpEF.